Enhanced adsorption of methylene blue onto graphene oxide-doped XFe2O4 (X = Co, Mn, Ni) nanocomposites: kinetic, isothermal, thermodynamic and recyclability studies / Bach Long Giang, Tran Van Thuan, Trinh Duy Nguyen, Pham Van Thinh, Do Sy Trung - Pham, Van Thinh
The nanocomposites XFe2O4/GO with various metal sites (X = Co, Mn, and Ni) were successfully synthesized via the polymerized complex method. The XFe2O4/GO family was characterized using X-Ray diffraction analysis, scanning electron microscopy (SEM), and a vibrating sample magnetometer. We also investigated the effect of three fundamental parameters (initial concentration, dosage, and pH) on the removal of methylene blue using the response surface methodology. A high F value, very low P value (< 0.00001), a non-significant lack of fit, and the determination coefficient (R 2 > 0.95) demonstrated a strong correlation between experimental and predicted values of the responses. The predicted optimal conditions for maximum removal efficiency were easily determined to adhere to the following trend for actual test experiments: MnFe2O4/GO (60.1%) < CoFe2O4/GO (80.3%) < NiFe2O4/GO (87.7%). Moreover, the adsorption behavior was well-described by the Langmuir isotherm and a pseudo-second-order kinetic model. The maximum capacity for adsorption of methylene blue onto XFe2O4/GO was found from 42.2 to 80.6 mg/g. Moreover, the XFe2O4/GO could be regenerated for several cycles without a considerable decrease in removal yield, suggesting that this highly promising XFe2O4/GO could be applied as an efficient and novel adsorbent.